Dynamique du carbone organique du sol et de l’azote dans une chronoséquence de plantation de Acacia auriculiformis A. Cunn. ex Benth. (Fabaceae), à Bambou-Mingali (République du Congo) - Mankessi François; Malonga Kiantouba Merveillia Gilfarde; Ifo Suspense Averti (European Scientific Journal, ESJ, 2022)
Dans le contexte international de réchauffement global, plusieurs initiatives sont prises par les pays, les organismes internationaux pour apporter une réponse appropriée qui permettrait de limiter la hausse de la température à 1,5° C, comme le recommande le rapport 1,5° du GIEC. La République du Congo est un pays fortement engagé dans les questions de lutte contre les changements climatiques à travers la gestion durable de ses forêts, la mise en place des plantations domaniales et industrielles, à base d’espèces endogènes et exotiques à croissance rapide dont de Acacia auriculiformis A. Cunn. ex Benth. Pour évaluer l’impact des plantations de Acacia auriculiformis A. Cunn. ex Benth sur la restitution du carbone et de l’azote au sol, une étude portant sur la dynamique du carbone et de l’azote organique du sol dans les plantations de la réserve foncière de Bambou-Mingali a été réalisée. Des échantillons de sol ont été prélevés sur les horizons 0-15 cm et 15-30 cm, d’une chronoséquence de 2, 3, 4, 5, 6, 7, et 8 ans de celles-ci ainsi que sur une savane pure, conformément aux directives du GIEC qui encouragent de collecter les échantillons sol entre 0 et 30 cm de profondeur. L’objectif général de ce travail a été d’évaluer le stock de carbone organique du sol sur une chronoséquence de sept âges de plantations de Acacia auriculiformis A. Cunn. ex Benth. In the international context of global warming, several initiatives are taken by countries, international organizations to provide an appropriate response that would limit the rise in temperature to 1.5 ° C, as recommended by the 1.5 report of the IPCC. The Republic of the Congo is a country strongly committed to issues of the fight against climate change through the sustainable management of its forests, the establishment of state and industrial plantations, based on endogenous and exotic species with rapid growth, including Acacia auriculiformis A. Cunn. ex Benth. To assess the impact of Acacia auriculiformis A. Cunn plantations. ex Benth on the return of carbon and nitrogen to the soil, a study on the dynamics of carbon and organic nitrogen in the soil in the plantations of the Bambou-Mingali land reserve was carried out. Soil samples were taken on the 0-15 cm and 15-30 cm horizons, with a chronosequence of 2, 3, 4, 5, 6, 7, and 8 years of these as well as on a pure savanna, in accordance with IPCC guidelines which encourage collecting soil samples between 0 and 30 cm depth. The general objective of this work was to assess the stock of organic carbon in the soil over a chronosequence of seven planting ages of Acacia auriculiformis A. Cunn. ex Benth..The soil samples collected by horizon and by plot were sieved, dried and conditioned in plastic bags for laboratory determination of carbon and total nitrogen by the Walkey and Black and Kjeldahl methods, respectively. The results obtained revealed an age effect on the nitrogen (P = 0.07619), carbon (P = 0.0050) and carbon stock (P = 0.0067) contents. The nitrogen and carbon contents as well as the soil organic carbon stocks were higher in the 8-year-old plantation with averages of 1.25 ± 0.33 mgN respectively. g-1; 15.87 ± 6.08 mgC.g-1 and 28.70 ± 9.48 t.ha-1 and lower in the 6-year-old plot respectively at 0.93 ± 0.05 mgN.g-1; 7.87 ± 0.58 mgC.g-1 and 15.57 ± 1.31 t.ha-1. The study also revealed a horizon effect on carbon and nitrogen contents with respective P-values of 0.0019 and 0.00015. The H0 horizon (0-15 cm) presented the highest stocks whatever the age of the plantation with an average of 32.98 ± 6.56 t.ha-1 in the 8-year-old plot against 16, 46 ± 1.13 t.ha-1 in the 6-year-old plot and on the H1 horizon (15-30 cm) an average of 24.42 ± 11.26 t.ha-1 in the 8-year-old plot against 14 , 69 ± 0.83 t.ha-1 in the 6-year-old plot. Also the C / N ratio is influenced by the age (P-value = 0.008) of the plantation and not by the horizon (P-value = 0.1243). Whatever the parameter considered, it emerges that age influences the return of carbon and nitrogen to the soil. Thus, there is an accumulation of carbon in the plantations of the Acacia auriculiformis chronosequence.